Genetic analysis of aluminum tolerance in Brazilian barleys - Minella, Euclydes; Sorrells, Mark Earl (Pesquisa Agropecuaria Brasileira, 2002)
Aluminum (Al) toxicity is a major factor limiting barley growth in acid soils, and genotypes with adequate level of tolerance are needed for improving barley adaptation in Brazil. To study the inheritance of Al tolerance in Brazilian barleys, cultivars Antarctica 1, BR 1 and FM 404 were crossed to sensitive Kearney and PFC 8026, and intercrossed. Parental, F1, F2 and F6 generations were grown in nutrient solution containing 0.03, 0.05 and 0.07 mM of Al and classified for tolerance by the root tip hematoxylin staining assay. Tolerant by sensitive F2 progenies segregated three tolerant to one sensitive, fitting the 3:1 ratio expected for a single gene. The F6 populations segregated one tolerant to one sensitive also fitting a monogenic ratio. The F2 seedlings from crosses among tolerant genotypes scored the same as the parents. Since the population size used would allow detection of recombination as low as 7%, the complete absence of Al sensitive recombinants suggests that tolerance in these cultivars is most probably, controlled by the same gene. Thus, the potential for improving Al tolerance through recombination of these genotypes is very low and different gene sources should be evaluated.